Status of the human embryo: Philosophical Foundations from Phenomenology (Revista Iberoamericana de Bioética, 2017)
Given the difficulty in demonstrating the moment of ontogenesis in which personalization takes place, we sought to define, from a philosophic point of view, the nature of the human embryo regarding its individuality, using Phenomenology, specifically reflections of philosophers Bourghet and Merleau-Ponty on the embryo. Although the statement of their individuality does not entail ethical content in itself, from the point of view of ethical responsibility, it is an extremely important fact to be considered in the bioethical reflection about the moment of ontogeny from which human life must (ethical duty) be protected.
Keywords: embryo; human; bioethics; philosophy; phenomenology